Etalululo lyembo “Omapuko gi igalala mokupopya, mokulesha nomokunyola melaka lyOshindonga” (ISBN: 978-99945-54-29-4) (JULACE: Journal of the University of Namibia Language Centre, 2024)
A REVIEW OF THE BOOK “COMMON ERRORS IN SPEAKING, READING AND WRITING IN OSHINDONGA LANGUAGE”Johannes ShifelaMinistry of Education, Arts and CultureThis paper reviews Oshindonga grammar book titled "Omapuko gi igalala mokupopya, mokulesha nokunyola mElaka lyOshindonga" (translated as "Common mistakes in speaking, reading and writing in Oshindonga language"). As the title says, the book is on Oshindonga language rules. This paper reveals that Oshindonga phonology and morphology are well presented in the present book. In addition, it discloses that the structure of a verb and the subject marker of Oshindonga are narrated effectively in this book. The paper further argues that the present book has a number of shortcomings, namely nontreatment of loanwords, uses of diphthongs that don’t exist in Oshindonga orthography, uses of a hyphen in complex words, uses of the disjunctive writing system in writing Oshindonga verbs and possessive nouns, uses of twelve noun classes in Oshindonga, as well as a number of few grammatical errors. Furthermore, it posits that Oshindonga orthography is unfit, hence there are mismatches between its sound system and its alphabetical representation. Finnegan (2011) as cited in Dube (2021, p.42) supports the finding above that orthography is a writing system that aims to match an alphabet’s representation of a language’s sound system. Therefore, orthographies that do present a difference between spoken and written language are deemed inappropriate. Moving forward, this paper identifies teachers, and lectures as some of the potential benefits as it could serve as guide to them in teaching Oshindonga according to Bantu languages word structure. Moreover, it is useful to learners, students, editors, authors and foreigners who are interested in learning Oshindonga language grammar rules. Lastly, this paper recommends Oshindonga orthography to be reviewed, because this book is based on the present Oshindonga orthography 3. The review of Oshindonga orthography 3 will permit the gap between its spoken language and its alphabetical representation to be filled.
Keywords: BOOK REVIEW